A Community Health Clinic Breastfeeding-Friendly Pilot: What Can We Learn about the Policy Process?. (November 2015) - Johnson, Donna B.; Lamson, Erica; Schwartz, Rachel; Goldhammer, Camie; Ellings, Amy
Background: Implementing evidence-based practices and policies for breastfeeding support in community clinics is a promising, but challenging, approach to reducing disparities in breastfeeding rates. Objective: This study aimed to apply a policy process research framework to increase knowledge of factors that facilitate adoption and implementation of breastfeeding policy changes. Methods: In 2013, Washington State piloted a process to encourage 8 clinics to adopt and implement steps to become breastfeeding friendly. Evaluation data were collected through interviews, project reports, training evaluations, and pre– and post–self-assessments of achievement of the steps. Results: In 6 months, clinics increased the breastfeeding-friendly steps that they were implementing from a median (interquartile range) of 1.5 (0-3) to 6 (5-7). Improvements were most likely in the steps that required the fewest resources and administrative changes. Barriers to implementation included misperceptions about breastfeeding and breastfeeding support; lack of administrative "buy-in"; need for organizational changes to accommodate actions like monitoring breastfeeding rates and allowing providers training time; and the social-political climate of the clinic. Several factors, including actions taken by public health practitioners, enhanced the change process. These included fostering supportive relationships, targeting technical assistance, and providing resources for planning and training. Conclusion: This pilot project demonstrates that it is possible to make changes in breastfeeding support practices and policies in community clinics. Recommendations to enhance future work include framing and marketing breastfeeding support in ways that resonate with clinic decision makers and enhancing training, resources, and advocacy to build capacity for internal and external systems changes to support breastfeeding best practices.